Criteria and Indicators for Sustainable Agroforestry Management: Homegarden Agroforestry System - Durai, M. V.; Sankar, S. (Indian Forester, 2013)
Iterative filtering and generation method (IFGM) process was adopted for developing and testing criteria and indicators (C and I) for sustainability of homestead farming in Kerala. It includes three processes viz., Filter I, Filter II and Filter III. Two hundred and forty four candidate sets of C and I were screened from various sources with Filter I and were reclustered into four guiding principles viz., a) Farming community well-being is assured, b) People well-being is assured, c) Homestead farmings' landscape health is assured and d) External environment is supportive to sustainable home gardens. At the end of field testing, 201 C and I were screened, which were subjected to Filter III. At the end of third process of IFGM, 176 appropriate C and I were identified for sustainable management of homestead farming. The rd maximum number of C and I were encountered under 3rd principle (homegardens' landscape health is assured) with 24 criteria and 68 indicators. At homestead management unit level, C and I may be used as a tool for monitoring direction of change towards/away from sustainability and undertaking corrective action.